2005
DOI: 10.1210/jc.2004-1024
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, the Metabolic Syndrome, and Nonalcoholic Fatty Liver Disease

Abstract: The findings stress the heterogeneous presentation of patients with the metabolic syndrome when the diagnosis is based on the broad Adult Treatment Panel III clinical criteria and demonstrate that those who are more insulin resistant have a higher prevalence of severe steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
156
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(178 citation statements)
references
References 25 publications
7
156
0
10
Order By: Relevance
“…The prevalence of diabetes mellitus in Iran is shockingly high, especially in young population [18] ; and it would not be hyperbolic to proclaim that diabetes mellitus is the mother of morbidity of all vital organs. Thus, for investigating organ damages induced by different diseases, independently, we have to censor the impact of diabetes mellitus in our patient population by excluding them from the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of diabetes mellitus in Iran is shockingly high, especially in young population [18] ; and it would not be hyperbolic to proclaim that diabetes mellitus is the mother of morbidity of all vital organs. Thus, for investigating organ damages induced by different diseases, independently, we have to censor the impact of diabetes mellitus in our patient population by excluding them from the study.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of NAFLD is not clearly defined, but there is a strong evidence in the literature that insulin resistance and visceral adiposity play major roles [18][19][20] . In our study, the prevalence of metabolic syndrome in patients with NAFLD was 26.4%, which is higher than that in the US general population (23.7%) [21] but is surprisingly lower than that reported in Iranian general population which was reported to be as high as 30%-31% [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study of 46 adults with NAFLD showed insulin resistance to be the strongest predictor of NAFLD, with fasting insulin levels nearly twice as high in patients with NAFLD as in controls. [26,15] NAFLD is also associated with an elevated serum triglycerides [27,28], low HDL-C [27], abnormal glucose regulation [29], and central adiposity [27], all features of the metabolic syndrome. A study of 30 non-obese adults with NAFLD and normal glucose tolerance showed these subjects to have significant insulin resistance and features of the MS, again implicating insulin resistance, even without obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that NAFLD often represents the hepatic component of the metabolic syndrome, which is characterized by obesity, hyperinsulinemia, peripheral insulin resistance, diabetes, and hypertension [3e6]. The reported prevalence of NAFLD in patients with diabetes is 40e80%, and it is frequently associated with obesity e mainly abdominal e hypertriglyceridemia, and high-normal levels of alanine aminotransferase (ALT) [7,8]. NAFLD has long been considered a benign disease, but recent studies show that in some cases it evolves into nonalcoholic steato-hepatitis (NASH) [9].…”
mentioning
confidence: 99%